Magnitude and predictors of elasticity of demand for morphine are similar in male and female rats - Harris, Andrew C.; Muelken, Peter; Liu, Shirelle X.; Smethells, John R.; LeSage, Mark G.; Gewirtz, Jonathan C. (Frontiers in Behavioral Neuroscience, 2024)
Introduction. Sex differences in vulnerability to opioid use disorder (OUD) have been reported in some clinical and preclinical studies, but findings are mixed and further research is needed in this area. The goal of this study was to compare elasticity of demand (reinforcement efficacy) in an i.v. morphine self-administration (SA) model in male and female rats using a translationally relevant behavioral economics approach. Rate of acquisition and predictors of individual differences in demand (e.g., cumulative morphine infusions during acquisition) were also evaluated in both sexes. Materials, Methods, and Results. Acquisition of morphine SA (0.4 mg/kg/inf) under a fixed ratio (FR) 1 schedule of reinforcement was slower and infusions earned were lower in females than in males (n = 30-31/sex), but infusions earned did not differ between sexes during the FR 2 and FR 3 phases of acquisition. Increases in the FR response requirement across sessions during demand testing (FR 1 - FR 96) resulted in a progressive reduction in morphine infusions in both sexes. Morphine consumption was well-described by an exponential demand function in both sexes and was associated with considerable individual vulnerability (≈ 20-fold range for both sexes). There were no sex differences in elasticity of demand (rate of decline in morphine consumption with increasing price) or intensity of demand (consumption at zero price). A higher number of infusions earned during the FR 2 and FR 3 phases of acquisition and greater maximum response rates during demand testing were associated with lower demand elasticity (i.e., greater reinforcing efficacy) in both males and females, whereas other relationships were sex-specific (e.g., higher intensity of demand was associated with lower elasticity of demand in males but not in females). Conclusions. Our findings indicate similar elasticity of demand and predictors of individual differences in demand for morphine in male and female rats, although sex differences were observed in initial rate of acquisition and in some correlations between morphine SA measures. These data are consistent with findings of similar OUD vulnerability in males and females in some human and animal studies.